Curing assistant, curing agent, cured body and method for producing the same
Patent Information
- Application Number
- JP2024147818
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-29
- Publication Date
- 2025-03-14
AI Technical Summary
【0018】 本発明によれば、原料の製造プロセスを含めて二酸化炭素の排出を削減することができ、国内の天然又は人工の資源を有効活用することができる硬化助剤、硬化剤及びそれらを用いた硬化体並びにその製造方法を提供できる。
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel curing aid and curing agent suitable for use in producing a hardened product for use in buildings and the like, a hardened product using the same, and a method for producing the same. [Background technology]
[0002] In order to prevent global warming, efforts are being made to reduce emissions of greenhouse gases such as carbon dioxide and to achieve carbon neutrality. For this reason, the manufacturing industry is also being asked to reduce carbon dioxide emissions during the manufacturing process as much as possible.
[0003] Concrete buildings use a large amount of hydraulic cement as a material, but Portland cement, which is the mainstream hydraulic cement, is an artificial cement that emits large amounts of carbon dioxide when fired at around 1450°C during its manufacturing process. Therefore, from the perspective of reducing carbon dioxide emissions, research is being conducted into hardened bodies and hardening methods that do not use Portland cement.
[0004] As part of this movement, there is research and development into hardened materials and hardening methods that use the pozzolanic reaction. The pozzolanic reaction is the hardening action of ancient cement, in which a soluble siliceous material reacts with calcium hydroxide in the presence of water to produce an insoluble compound that hardens. Hardened materials and hardening methods that use the pozzolanic reaction do not require firing Portland cement, making it possible to significantly reduce carbon dioxide emissions.
[0005] Pozzolans are soluble siliceous materials that are not hydraulic themselves but undergo the above-mentioned pozzolanic reaction. There are two types of pozzolans: artificial pozzolans, such as fly ash discharged from thermal power plants and silica fume produced when ferrosilicon or silicon metal is manufactured in an electric arc furnace, and natural pozzolans, such as natural volcanic ash. Pozzolans have traditionally been used as an admixture for concrete or as an admixture for blended cement. However, the global trend toward reducing carbon dioxide emissions requires materials that do not use fly ash discharged from thermal power plants or silica fume produced in electric arc furnaces. Shirasu, known as a natural pozzolan, has low pozzolanic reactivity and does not meet the JIS standard as is. Conventional hardened bodies and hardening methods that utilize pozzolans in this way have mainly used artificial pozzolans as admixtures for concrete or as admixtures for mixed cement.
[0006] Hydraulic lime is a binder that emits less carbon dioxide than cement. There are natural hydraulic lime, which is produced by burning clayey limestone, which is produced in limited areas, and artificial hydraulic lime, which is made by mixing clayey limestone with water and burning it at 1000°C or higher. Regarding artificial hydraulic lime, there is a hydraulic lime composition that contains a porazon material with a specific surface area and average particle size and slaked lime (Patent Document 1). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2013-519616 Summary of the Invention [Problem to be solved by the invention]
[0008] The hydraulic lime composition described in Patent Document 1 is made of a commercially available pozzolanic material and hydrated lime, and has a compressive strength of 1.8 MPa or less, which does not meet the strength required for ordinary concrete in buildings and civil engineering works. The pozzolanic material contains a material that unavoidably emits a large amount of carbon dioxide during its production.
[0009] The present invention aims to provide a novel hardening assistant and hardener suitable for use in producing a hardened body that can reduce carbon dioxide emissions, including the raw material production process, and can effectively utilize domestic natural or artificial resources, as well as a hardened body using the same, and a production method thereof. [Means for solving the problem]
[0010] In the course of their research into the effective use of shirasu, the inventors have been researching how to increase the reactivity of volcanic glass, the main component of shirasu and obtained by classifying shirasu, and how to use it as a hardening agent to replace cement. They have found that chemical treatment of volcanic glass using an alkaline solution and an acid produces a colloidal solution in which aluminosilicate ions are condensed (aluminosilicate sol) and precipitated particles activated by the chemical treatment (aluminosilicate activated particles), and that each of these aluminosilicate sol and aluminosilicate activated particles, as well as a suspension containing both, can be used as a hardening assistant and even a hardening agent.
[0011] The present invention is derived from the above findings. That is, the hardening aid of the present invention is prepared by adding an inorganic acid to a suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic eruptions or artificial pozzolan, and contains aluminosilicate activated particles and aluminosilicate sol.
[0012] The hardening aid of the present invention also contains aluminosilicate activated particles (including dealkalized aluminosilicate activated particles) which are the solid phase obtained by solid-liquid separation from an activated suspension produced by adding an inorganic acid to a suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan. The hardening aid of the present invention also contains aluminosilicate activated particles (the aluminosilicate activated particles include those which have been dealkalized) which have been activated by adding an inorganic acid to aluminosilicate particles in the solid phase which have been separated from the solid-liquid portion of a suspension produced by the heating and alkali treatment of volcanic glass material derived from volcanic ejecta or artificial pozzolan.
[0013] The hardening aid of the present invention contains aluminosilicate sol, which is the liquid phase obtained by solid-liquid separation from an activated suspension produced by adding an inorganic acid to a suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan. The hardening aid of the present invention contains an aluminosilicate sol that has been activated by adding an inorganic acid to the liquid phase that has been separated from the solid-liquid separation of a suspension produced by heating and alkali treating volcanic glass derived from volcanic ejecta or artificial pozzolan.
[0014] The hardening assistant of the present invention may be in the form of a dried solid. The aluminosilicate activated particles may be specifically particles having a core of either or both of volcanic glass and zeolite, the surface of which is covered with aluminosilicate gel, and the aluminosilicate gel may be dissolved and precipitated from the core to form an active layer on the surface of the particles.
[0015] The method for producing a hardening aid of the present invention includes the steps of heating and mixing volcanic glass or artificial pozzolan derived from volcanic ejecta with an alkaline solution to produce a suspension, and adding an inorganic acid to one or both of the solid and liquid phases of the suspension. The method may include a step of subjecting the solid phase of the suspension to a dealkalization treatment. After the step of adding an inorganic acid to both the solid and liquid phases of the suspension, the method may include a step of subjecting the obtained activated suspension to solid-liquid separation to obtain aluminosilicate activated particles of the solid phase, in which case the method may include a step of subjecting the aluminosilicate activated particles of the solid phase to a dealkalization treatment. After the step of adding an inorganic acid to both the solid and liquid phases of the suspension, the method may also include a step of subjecting the obtained activated suspension to solid-liquid separation to obtain an aluminosilicate sol of the liquid phase. The method may further include a step of drying and solidifying.
[0016] The hardening agent of the present invention contains the above-mentioned hardening assistant and a calcium source. The calcium source can be surface-modified lime or cement. The method for producing the hardener of the present invention also includes a step of mixing the hardening assistant with a calcium source. The calcium source may be surface-modified lime or cement.
[0017] The method for producing a hardened body of the present invention includes a step of mixing the raw materials containing the above-mentioned hardening assistant, a calcium source, and water, a step of forming the raw materials, and a step of curing the raw materials. Specifically, the calcium source is a compound that releases calcium ions under wet conditions. The calcium source can be surface-modified lime or cement. Effect of the Invention
[0018] According to the present invention, it is possible to provide a hardening aid, a hardener, and a hardened body using the same, as well as a manufacturing method thereof, which can reduce carbon dioxide emissions including the manufacturing process of the raw materials and can effectively utilize domestic natural or artificial resources. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The curing aid, curing agent, cured product, and method for producing the same of the present invention will now be described in more detail. [Curing agent] (Embodiment 1) The hardening aid of embodiment 1 is prepared by adding an inorganic acid, such as sulfuric acid, to a suspension produced by heating and alkali treating volcanic glass derived from volcanic ejecta or artificial pozzolan, and contains aluminosilicate activated particles and aluminosilicate sol.
[0020] Volcanic glass is a natural pozzolan containing aluminosilicate. Volcanic glass originates from volcanic eruptions such as shirasu, and can be obtained by classifying the volcanic eruptions to reduce the mineral content. This volcanic glass reacts with a calcium source, such as calcium hydroxide, to become hydraulic. However, the hardened body made from volcanic glass as is has a small hardening effect.
[0021] The hardening aid of this embodiment is made of volcanic glass or artificial pozzolan derived from volcanic ejecta. The volcanic glass or artificial pozzolan derived from volcanic ejecta is heated and mixed with an alkaline solution. This treatment is referred to as a heating and alkaline treatment in this specification. A suspension containing aluminosilicate particles covered with a high concentration of aluminosilicate ions and aluminosilicate ions is generated by the heating and alkaline treatment. When an inorganic acid is added to this suspension, the aluminosilicate ions condense to generate colloidal particles with a particle size of 0.1 μm or less, which are suspended in the liquid. At the same time, the surfaces of the aluminosilicate particles are modified into aluminosilicate gel to become activated aluminosilicate activated particles. A suspension containing the aluminosilicate activated particles and aluminosilicate sol is referred to as an activated suspension in this specification. Furthermore, aluminosilicate particles with activated surfaces are referred to as aluminosilicate activated particles in this specification. Furthermore, a suspension obtained by excluding aluminosilicate activated particles from an active suspension is an aluminosilicate sol. That is, the activated suspension contains aluminosilicate activated particles and aluminosilicate sol. This activated suspension can react with a calcium source to obtain a hardened body with high strength. The hardening assistant of the present embodiment is an embodiment in which the hardening assistant is this activated suspension.
[0022] Both the aluminosilicate activated particles and the aluminosilicate sol are rapid setting pozzolans that react with a calcium source to become hydraulic. Moreover, they have higher activity than the raw volcanic glass or artificial pozzolans before being heated and mixed with an alkaline solution and then added with an inorganic acid. Therefore, when the aluminosilicate activated particles and the aluminosilicate sol are mixed with a calcium source to form a hardened body, high strength (compressive strength) can be obtained in a shorter curing period. Furthermore, during curing, carbon dioxide in the air is absorbed, increasing the strength compared to immediately after molding. This makes it possible to obtain a hardened body with a compressive strength equivalent to that of normal concrete. Since air can be used as a carbon dioxide source for improving strength, the hardened body can absorb carbon dioxide and be strengthened simply by leaving it in the air.
[0023] The volcanic glass material derived from volcanic ejecta is obtained by, for example, classifying shirasu, so that firing or calcination is not required, and therefore, the preparation of the raw material does not involve the emission of a large amount of carbon dioxide. In addition, the process of heating and mixing the volcanic glass material derived from volcanic ejecta with an alkaline solution and further adding an inorganic acid to obtain an activated suspension can be carried out at a temperature of 100°C or less in the aqueous solution, so energy consumption is low, and the amount of carbon dioxide emitted is also low in this respect. Furthermore, the hardened body produced using the hardening assistant has high strength without necessarily requiring the addition of Portland cement, which has a large environmental impact, so it is also excellent in environmental performance in this respect. Furthermore, since the hardened body can absorb carbon dioxide, when the amount of carbon dioxide emitted in the process from the raw material to the production of the hardened body and the amount of carbon dioxide absorbed by the molded body are calculated comprehensively, the amount of carbon dioxide emitted is extremely small, making it possible to aim for carbon neutrality.
[0024] Shirasu, the raw material used to obtain volcanic glass derived from volcanic ejecta, is a mixture of minerals and volcanic glass that were erupted and deposited by the eruption of the Aira Caldera, and although it is said to have nearly inexhaustible reserves, it has been considered difficult to utilize as a resource because the particle sizes range widely from gravel to fine particles. In recent years, technology has been developed to separate shirasu by composition and particle size, such as sand, pumice, fine volcanic glass powder, and clay (Patent No. 6458267), and as a result, fine volcanic glass powder has been standardized as JIS A6209, and it is expected to be used as a concrete material.
[0025] The hardening assistant of this embodiment provides a new way to utilize shirasu, apart from the above-mentioned volcanic glass fine powder, by heating and mixing glassy material derived from volcanic ejecta such as shirasu with an alkaline solution, and then adding an inorganic acid to obtain an activated suspension, which is then utilized as a hardening assistant. Both the aluminosilicate activated particles and the aluminosilicate sol in the activated suspension are used as binders, so there is no waste and the volcanic glassy material can be utilized effectively.
[0026] As a raw material for the hardening aid, it is possible to use artificial glassy pozzolan, similar to the volcanic glass mentioned above. Even if artificial pozzolan such as fly ash discharged from a thermal power plant is used, the hardening aid can be produced by heating and mixing it with an alkaline solution and adding an inorganic acid using this method. Fly ash is an industrial by-product that produces CO 2 The emissions are set low at 19.6 kg / t, making it highly practical.
[0027] The hardening aid of the present embodiment preferably has a pH of 1 to 11. The pH of the hardening aid is an index reflecting the amount of sulfuric acid added when the hardening aid is prepared, and when the pH is in the range of 1 to 11, the compressive strength of the hardened body produced using the hardening aid can be effectively increased. When the pH is less than 1 or exceeds 11, the compressive strength of the hardened body is not sufficiently high.
[0028] (Embodiment 2) The hardening aid of the second embodiment contains aluminosilicate activated particles of the solid phase obtained by solid-liquid separation from an activated suspension produced by adding an inorganic acid to a suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan. The aluminosilicate activated particles include those that have been dealkalized.
[0029] The hardening aid of this embodiment focuses on the solid phase of the aluminosilicate sol obtained by solid-liquid separation from the activated suspension. The aluminosilicate activated particles are rapid-setting pozzolans as described above, and have hydraulic properties when reacting with a calcium source. Moreover, they have higher activity than the raw volcanic glass and artificial pozzolans. Therefore, when the aluminosilicate particles and a calcium source are mixed to form a hardened body, high strength (compressive strength) can be obtained in a shorter curing period. Furthermore, during curing, carbon dioxide in the air is absorbed, and the strength increases compared to immediately after molding. This makes it possible to obtain a hardened body having a compressive strength equivalent to that of normal concrete. Since air can be used as a carbon dioxide source for improving strength, the hardened body can absorb carbon dioxide and be strengthened simply by leaving it in the air. The aluminosilicate activated particles include those that have been subjected to dealkalization treatment after solid-liquid separation of an activated suspension. When a hardening aid containing dealkalized aluminosilicate activated particles is mixed with a calcium source to form a hardened body, it can produce a hardened body with high strength, particularly when the calcium source is cement. This is thought to be because, when the calcium source is cement, the dealkalization treatment of the hardening aid prevents the alkali-aggregate reaction and the pozzolanic reaction caused by the aluminosilicate activated particles becomes dominant, thereby increasing the strength.
[0030] The hardening aid of the present embodiment preferably has a pH of 1 to 11. The pH of the hardening aid is an index reflecting the amount of sulfuric acid added when the hardening aid is prepared, and when the pH is in the range of 1 to 11, the compressive strength of the hardened body produced using the hardening aid can be effectively increased. When the pH is less than 1 or exceeds 11, the compressive strength of the hardened body is not sufficiently high.
[0031] (Embodiment 3) The hardening aid of the third embodiment includes a hardening aid containing aluminosilicate activated particles that are activated by adding an inorganic acid to aluminosilicate particles in the solid phase that is separated from the suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan. The aluminosilicate activated particles include those that have been dealkalized.
[0032] The hardening aid in the above-mentioned second embodiment was aluminosilicate particles obtained by solid-liquid separation from an activated suspension. The hardening aid in this embodiment is not obtained by solid-liquid separation of an activated suspension as in the second embodiment, but by solid-liquid separation of a suspension produced by heating and alkali treating volcanic glass derived from volcanic ejecta or artificial pozzolan. An inorganic acid is then added to the aluminosilicate particles, which are the solid phase of the solid-liquid separation, to activate them and obtain aluminosilicate activated particles. The hardening aid in this embodiment is an embodiment that contains the aluminosilicate activated particles.
[0033] The hardening assistant of this embodiment has a relatively low content of simple aluminosilicate gel compared to the hardening assistant of embodiment 2, and is easier to densify, so it is considered to be advantageous as a hardening assistant. As mentioned above, the aluminosilicate activated particles are a rapid-setting pozzolan that reacts with a calcium source to become hydraulic. Moreover, they have higher activity than the raw volcanic glass and artificial pozzolans. Therefore, when the aluminosilicate activated particles are mixed with a calcium source to form a hardened body, high strength (compressive strength) can be obtained in a shorter curing period. Furthermore, during curing, carbon dioxide in the air is absorbed, increasing the strength compared to immediately after molding. This makes it possible to obtain a hardened body with a compressive strength equivalent to that of ordinary concrete. Since air can be used as a carbon dioxide source for improving strength, the hardened body can be increased in strength by simply leaving it in the air, where it absorbs carbon dioxide. The aluminosilicate activated particles include aluminosilicate particles that have been activated by adding an inorganic acid and then dealkalized. When a hardening aid containing dealkalized aluminosilicate activated particles is mixed with a calcium source to form a hardened body, it can produce a hardened body with high strength, particularly when the calcium source is cement. This is thought to be because, when the calcium source is cement, the dealkalization of the hardening aid prevents the alkali-aggregate reaction and the pozzolanic reaction caused by the aluminosilicate activated particles becomes dominant, thereby increasing the strength.
[0034] The hardening aid of the present embodiment preferably has a pH of 1 to 11. The pH of the hardening aid is an index reflecting the amount of sulfuric acid added when the hardening aid is prepared, and when the pH is in the range of 1 to 11, the compressive strength of the hardened body produced using the hardening aid can be effectively increased. When the pH is less than 1 or exceeds 11, the compressive strength of the hardened body is not sufficiently high.
[0035] (Embodiment 4) The hardening aid of embodiment 4 contains an aluminosilicate sol of the liquid phase obtained by solid-liquid separation from an activated suspension produced by adding an inorganic acid to a suspension produced by heating and alkali treating volcanic glass derived from volcanic ejecta or artificial pozzolan. The hardening assistant of the above-mentioned embodiment 2 contains the aluminosilicate activated particles of the solid phase of the activated suspension separated from the solid-liquid phase. The hardening assistant of the present embodiment focuses on the aluminosilicate sol of the liquid phase.
[0036] As explained in the first embodiment, the aluminosilicate sol is a rapid setting pozzolan, and reacts with a calcium source to obtain hydraulic properties. Moreover, it has higher activity than the raw material volcanic glass or artificial pozzolan before it is heated and mixed with an alkaline solution and further added with an inorganic acid. Therefore, when the aluminosilicate sol is mixed with a calcium source to obtain a hardened body, high strength (compressive strength) can be obtained in a shorter curing period. Furthermore, during curing, carbon dioxide in the air is absorbed, and the strength increases compared to immediately after molding. This makes it possible to obtain a hardened body having a compressive strength equivalent to that of normal concrete. Since air can be used as a carbon dioxide source for improving strength, the hardened body can absorb carbon dioxide and be strengthened simply by leaving it in the air.
[0037] The hardening aid of the present embodiment preferably has a pH of 1 to 11. The pH of the hardening aid is an index reflecting the amount of sulfuric acid added when the hardening aid is prepared, and when the pH is in the range of 1 to 11, the compressive strength of the hardened body produced using the hardening aid can be effectively increased. When the pH is less than 1 or exceeds 11, the compressive strength of the hardened body is not sufficiently high.
[0038] (Embodiment 5) The hardening aid of embodiment 5 contains an aluminosilicate sol obtained by adding an inorganic acid to an aluminosilicate aqueous solution in the liquid phase obtained by solid-liquid separation from a suspension produced by heating and alkali treating volcanic glass derived from volcanic ejecta or artificial pozzolan. The hardening aid of the above-mentioned embodiment 4 was an aluminosilicate sol obtained by solid-liquid separation from an activated suspension. The hardening aid of this embodiment is not obtained by solid-liquid separation of an activated suspension as in embodiment 4, but by solid-liquid separation of a suspension produced by heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan. Then, an inorganic acid is added to the aluminosilicate aqueous solution, which is the liquid phase of the solid-liquid separation, to activate it and obtain an aluminosilicate sol. The hardening aid of this embodiment is an embodiment that contains this aluminosilicate sol.
[0039] As mentioned above, aluminosilicate sol is a rapid-setting pozzolan that reacts with a calcium source to become hydraulic. Moreover, it has higher activity than the raw volcanic glass or artificial pozzolan before it is heated and mixed with an alkaline solution and then inorganic acid is added. Therefore, when aluminosilicate sol is mixed with a calcium source to form a hardened body, high strength (compressive strength) can be obtained in a shorter curing period. Furthermore, during curing, carbon dioxide in the air is absorbed, increasing the strength compared to immediately after molding. This makes it possible to obtain a hardened body with a compressive strength equivalent to that of ordinary concrete. Since air can be used as a carbon dioxide source for improving strength, the hardened body can absorb carbon dioxide and be strengthened simply by leaving it in the air.
[0040] The hardening aid of the present embodiment preferably has a pH of 1 to 11. The pH of the hardening aid is an index reflecting the amount of sulfuric acid added when the hardening aid is prepared, and when the pH is in the range of 1 to 11, the compressive strength of the hardened body produced using the hardening aid can be effectively increased. When the pH is less than 1 or exceeds 11, the compressive strength of the hardened body is not sufficiently high.
[0041] (Embodiment 6) The hardening assistants of the above-mentioned first to fifth embodiments include those in a water-containing state, but may be those obtained by dehydrating and drying the hardening assistants in a water-containing state. The term "drying" as used in the present invention is not limited to complete drying, but refers to a hardening assistant having a solid content concentration of 40 mass% or more after dehydration or solid-liquid separation from a water-containing state, and water may remain. The hardening assistant of the sixth embodiment is in this dried form. The aluminosilicate activated particles of the second and third embodiments are dried to become high-density aluminosilicate activated particles. The aluminosilicate sol is dried to become an aluminosilicate gel. The curing aid of the present embodiment, which is a dried curing aid, has the advantages of being lighter in mass, having excellent storage stability, being easier to formulate, and being easier to handle, compared to a curing aid in a water-containing state.
[0042] (Embodiment 7) The curing aid of embodiment 7 is a specific embodiment of the aluminosilicate-activated particles in the curing aid of any one of embodiments 1 to 3. That is, the aluminosilicate-activated particles are particles having a core of either or both of volcanic glass and zeolite, the surface of which is covered with aluminosilicate gel, and the aluminosilicate gel is dissolved and precipitated from the core to form an active layer on the surface of the particles.
[0043] The aluminosilicate activated particles are particles whose cores are either or both of volcanic glass and zeolite, the surface of which is covered with aluminosilicate gel. The zeolite is produced by an alkali precipitation reaction of the raw volcanic glass. The aluminosilicate gel covering the surface of the aluminosilicate activated particles serves as an active layer for the pozzolanic reaction. The formation and extent of the active layer can be confirmed by the increase in the volume of the activated particles that have settled after chemical treatment, the fact that the BET specific surface area of the dried aluminosilicate activated particles is larger than that of the aluminosilicate particles, and the increase in the consumption rate of slaked lime when the hardened body is produced.
[0044] The aluminosilicate sol in the curing aid of either of the above-mentioned embodiments 4 and 5 is a colloidal solution in which aluminosilicate ions are condensed. The solid content is preferably 10 to 20% by mass. If the solid content is less than 10% by mass, the amount of the target component is reduced and the desired strength cannot be obtained. If the solid content is more than 20% by mass, the dispersion of the colloidal particles is likely to become non-homogenous, leading to a decrease in the performance of the cured body. The particles are fine particles with a particle size of 0.1 μm or less, have a large specific surface area, and are active.
[0045] [Method of manufacturing the curing agent] The method for producing the hardening aid of this embodiment includes the steps of heating and mixing volcanic glass or artificial pozzolan derived from volcanic ejecta with an alkaline solution to produce a suspension, and adding an inorganic acid to one or both of the solid and liquid phases of the suspension.
[0046] A suspension is produced by heating and mixing volcanic glass or artificial pozzolan derived from volcanic ejecta with an alkaline solution. If this suspension is not subjected to solid-liquid separation, that is, if an inorganic acid is added to both the solid phase and the liquid phase to produce an active suspension, the hardening aid of embodiment 1 is obtained. If the active suspension is subjected to solid-liquid separation to obtain a solid phase, the hardening aid of embodiment 2 is obtained. The hardening aid of embodiment 2 can also be dealkalized after obtaining the solid phase. If the above suspension is subjected to solid-liquid separation to obtain aluminosilicate particles of the solid phase, and an inorganic acid is added to the aluminosilicate particles, the hardening aid of embodiment 3 is obtained. The hardening aid of embodiment 3 can also be dealkalized after adding an inorganic acid. In addition, the active suspension is subjected to solid-liquid separation to obtain a liquid phase, thereby obtaining the curing aid of embodiment 4. In addition, the above suspension is subjected to solid-liquid separation to obtain a liquid phase, and an inorganic acid is added to this liquid phase, thereby obtaining the curing aid of embodiment 5.
[0047] First, the volcanic glass derived from the raw volcanic ejecta will be described. The volcanic glass derived from the volcanic ejecta can be volcanic glass granules with a volcanic glass content of 80% by mass or more classified from the volcanic ejecta, or volcanic glass fine powder obtained by pulverizing the volcanic glass granules. The volcanic ejecta is, for example, shirasu. By classifying the volcanic glass content to 80% by mass or more, the amount of minerals other than the volcanic glass, such as quartz and feldspar, can be reduced, and the strength of the hardened body can be increased. The volcanic glass granules have a particle size in the range of 0.05 mm to 0.6 mm, and the volcanic glass fine powder has a particle size in the range of 0.001 mm to 0.05 mm.
[0048] For example, the technology of Patent No. 6458267 can be used to classify volcanic ejecta. The technology of Patent No. 6458267 removes gravel with a particle size of more than 5 mm from volcanic ejecta, supplies the remaining part to an air table type specific gravity difference separator that vibrates a perforated plate tilted at a predetermined angle from the horizontal direction and blows air toward the perforated plate from below, and separates the gravel with a density of 2.5 g / cm3 discharged from an outlet on the upstream side of the perforated plate of the specific gravity separator. 3The above weight density and the density of the material discharged from the outlet on the downstream side of the perforated plate of the specific gravity separator are 2.5 g / cm 3 The fine aggregate is separated from the heavy specific gravity fraction or from the heavy specific gravity fraction and the perforated plate fraction, and the fine aggregate is separated to obtain a residual volcanic glass material obtained by separating the fine aggregate from the heavy specific gravity fraction or from the heavy specific gravity fraction and the perforated plate fraction, and the residual volcanic glass material obtained by separating the fine aggregate from the heavy specific gravity fraction or from the perforated plate fraction, and the residual volcanic glass material obtained by separating the fine aggregate from the heavy specific gravity fraction and the perforated plate fraction is obtained by pulverizing at least one of the separated volcanic glass material having a particle size of 0.05 mm to 0.3 mm, the volcanic glass material having a particle size of less than 0.05 mm, and the pumice made of volcanic glass having a particle size of 0.3 mm or more, by the technology of the above-mentioned Patent No. 6458267. The pulverizing means can be, for example, a vibration mill. In addition to the vibration mill, various mills such as a roller mill and a jet mill can also be used.
[0049] The volcanic glass material derived from volcanic ejecta can be volcanic glass granules obtained by classifying volcanic ash or volcanic rocks produced by quenching magma, or volcanic glass fine powder obtained by grinding or pulverizing the volcanic glass granules. The volcanic glass granules have a particle size in the range of 0.05 mm to 0.6 mm, similar to the volcanic glass granules classified from the volcanic ejecta described above, and the volcanic glass fine powder has a particle size in the range of 0.001 mm to 0.05 mm, similar to the volcanic glass fine powder classified from the volcanic ejecta described above. In recent years, large amounts of volcanic ash and pumice (volcanic rocks) produced by the eruptions of undersea volcanoes have washed up on coastlines, sometimes adversely affecting fishing, passenger ship operations, and aesthetics. However, rather than treating this volcanic ash and pumice (volcanic rocks) as a nuisance, they can be effectively utilized by using them as the raw materials for the volcanic glass of this embodiment.
[0050] For classification of volcanic ash or volcanic rock, for example, the technology of the above-mentioned Patent No. 6458267 can be used. As the pulverizing means, a vibration mill can be exemplified. In addition to the vibration mill, various mills such as a roller mill and a jet mill can also be used. As the grinding means, for example, a thoron mill can be used.
[0051] In addition, as with the volcanic glass mentioned above, artificial pozzolans can be used as raw materials. For example, artificial pozzolans such as fly ash discharged from thermal power plants can be used to create a hardening aid by heating and mixing it with an alkaline solution and adding an inorganic acid using this method. Fly ash is an industrial by-product that is produced by CO 2 The emissions are set low at 19.6 kg / t, making it highly practical.
[0052] Next, the alkaline solution to be mixed with the volcanic glass or artificial pozzolan derived from volcanic ejecta will be described. The alkaline solution is, for example, an aqueous solution of caustic soda. The concentration of caustic soda is preferably in the range of 0.5 to 3 mol / L. If it exceeds 3 mol / L, a uniform active suspension cannot be obtained. If it is less than 0.5 mol / L, the reactivity of the active suspension decreases. A more preferable concentration range of caustic soda is 0.8 to 2 mol / L. In addition to the aqueous solution of caustic soda, an aqueous solution of caustic potash or the like can be used. When the caustic soda is in the above concentration range and the concentration is low, the core of the aluminosilicate particle has a crystal structure mainly composed of volcanic glass, and when the concentration is high, the core of the aluminosilicate particle has a crystal structure mainly composed of zeolite. The heating temperature of the alkaline solution is preferably in the range of 80 to 150°C. The reaction proceeds when heated to 80°C or higher. Heating to a temperature above 150°C is not practical because the reaction apparatus becomes large. A more preferable temperature is 90 to 100°C.
[0053] Volcanic glass or artificial pozzolan derived from volcanic ejecta is stirred in a heated alkaline solution. The suspension needs only to elute aluminosilicate ions, and the stirring conditions vary depending on the solid-liquid ratio, heating temperature, air pressure, and type and concentration of the alkali. There are no restrictions on the stirring time, but it has been confirmed that a suspension of sufficient concentration can be obtained with approximately two hours under atmospheric pressure conditions. Therefore, it is preferable to stir for at least two hours.
[0054] Next, the inorganic acid to be gradually added to one or both of the solid phase and the liquid phase of the suspension will be described. The inorganic acid is, for example, sulfuric acid. Dilute sulfuric acid can be used as the sulfuric acid. It is preferable to add sulfuric acid in an amount such that the pH of the solution after addition is 1 to 11. By adjusting the pH to 1 to 11, an activated suspension in which aluminosilicate activated particles and aluminosilicate sol are generated in a liquid in which sodium sulfate is dissolved can be obtained. In addition to sulfuric acid and hydrochloric acid, carbonic acid can be used as the inorganic acid. Carbonic acid can be used by blowing carbon dioxide gas into the liquid or adding a liquid in which carbon dioxide is dissolved. When blowing carbon dioxide gas into the liquid, the carbon dioxide gas may be a gas containing a certain concentration of carbon dioxide, and a gas with a carbon dioxide concentration of about 0.04 volume % or higher can be used.
[0055] When the suspension or the activated suspension is subjected to solid-liquid separation, the solid-liquid separation means may be, for example, a centrifuge.
[0056] In the above-mentioned method for producing a curing aid, a step of drying can be carried out after the step of adding an inorganic acid. By drying, the mixture of aluminosilicate activated particles and aluminosilicate sol obtained by adding an inorganic acid, aluminosilicate activated particles or aluminosilicate sol is dried and solidified, preferably into powder. As a means for drying, for example, a low-temperature dryer used for thermostatic, dehumidifying, air drying, freeze drying, etc. can be used.
[0057] Next, the dealkalization treatment in the curing assistant of the second embodiment and the curing assistant of the third embodiment will be described. The dealkalization treatment is a process in which the aluminosilicate-activated particles are suspended in water to elute the alkaline components and sulfate ions, and the eluted water is removed, in order to remove alkaline components such as sodium sulfate (a by-product produced by the alkali and acid treatments) adhering to the aluminosilicate-activated particles. By repeating this dealkalization treatment, the aluminosilicate-activated particles are dealkalized. The present inventors have found that this dealkalization treatment has a strength-increasing effect that could not be predicted from conventional knowledge, particularly when the calcium source of the hardener is cement.
[0058] The degree of the dealkalization treatment can be indicated by the electrical conductivity of the suspension when the treated hardening aid is suspended in a certain amount of water and the solid content concentration is adjusted to 10 to 13 mass %. Specifically, the hardening reactivity can be improved by adjusting the electrical conductivity to 1 to 1000 mS / m. It is preferably 400 mS / m or less, and more preferably 100 mS / m or less. When the electrical conductivity of the suspension exceeds 1000 mS / m, the dealkalization treatment is insufficient. If the dealkalization treatment is repeated too many times, the activation layer on the surface of the aluminosilicate activated particles may decrease, and the pozzolanic effect may decrease. The hardening reactivity can be indicated by the activity index of the hardened body (measured according to JIS A6207). That is, it can be indicated by the value (x / y)% obtained by dividing the compressive strength (x MPa) of a mortar prepared by replacing 10% by weight of cement with an admixture by the compressive strength (y MPa) of a mortar prepared without replacing with an admixture. According to experiments by the present inventors, it was found that the 13w activity index (index when standard water curing was carried out for 13 weeks) reached a maximum of 134 by providing a dealkalization step, and therefore the dealkalization step was effective.
[0059] [Hardening agent] The hardening agent of this embodiment contains the hardening aid of any one of the above-mentioned embodiments 1 to 7 and a calcium source. In the presence of water, the hardening aid and the calcium source react with each other to harden. At this time, not only the pozzolanic reaction layer due to the aluminosilicate gel but also ettringite is generated by the by-product sodium sulfate, which further enhances the hardening action. Therefore, the hardening aid and the calcium source are stored separately until just before hardening, or the hardening aid and the calcium source are mixed in a water-free state. The hardening aid can be any of the hardening aids of the above-mentioned embodiments 1 to 7. It may be a dried hardening aid or a hardening aid that is not dried.
[0060] The calcium source may be any compound that releases calcium ions when wet. Specifically, there is slaked lime, which is a compound containing calcium hydroxide. Quicklime can also be used. In addition to industrial by-products and industrial waste of mineral or biological origin that release calcium ions when wet, cement and hydraulic lime can also be used. Since lime, which is abundant in Japan, can be used as the calcium source, it is possible to manufacture hardened bodies using domestic resources. The purity of the calcium source does not necessarily need to be high, so it is possible to use low-purity limestone that has not been used even though it is a large resource. Surface-modified lime can also be used as the calcium source. Surface-modified lime refers to lime particles in which only the particle surface is decarbonated and quicklimeized while the inside of the particle maintains the composition of calcium carbonate. Surface-modified lime can be produced by heat-treating limestone and quicklimeizing only the surface. Surface-modified lime can be used not only as a calcium source, but also as an aggregate. Heat treatment for producing surface-modified lime only needs to convert the surface into quicklime, which can be achieved by heating for a few seconds or less in a high-temperature air current of about 1000°C using a shirasu balloon manufacturing device using a medium fluidized bed as described in Patent No. 3028474. Therefore, compared with quicklime, which requires long-term high-temperature burning of limestone, and slaked lime, which is produced by slaked quicklime, surface-modified lime can significantly reduce the energy required for production. Although surface-modified lime shows strong alkalinity after dispersion in water, it has the characteristic that the particles disintegrate due to the slaked reaction like quicklime, and maintain their particle size even in water without decomposition. When the hardening aid is a dealkalized aluminosilicate-activated particle, the calcium source is preferably a cement. By combining the calcium source, which is a cement, with the dealkalized aluminosilicate-activated particle, a hydraulic hardener exhibiting high strength can be obtained. Here, the cement includes Portland cement and mixed cements containing Portland cement, specifically blast furnace cement, silica cement, fly ash cement, etc.
[0061] The mixing ratio of the hardening aid to the calcium source is preferably 0.2 to 2.0 in terms of the hardening aid / calcium source mass ratio when the calcium source is slaked lime. When the ratio is less than 0.2 or exceeds 2.0, it is difficult to obtain sufficient compressive strength when the hardened body is formed. Similarly, when the calcium source is cement, the ratio is preferably 0.2 to 2.0.
[0062] [Method of manufacturing the curing agent] The method for producing the hardener of this embodiment includes a step of mixing any one of the hardening assistants of the above-mentioned embodiments 1 to 7 with a calcium source. The hardening assistant and the calcium source are as described in the description of the hardener above. The above-mentioned surface-modified lime can also be used as the calcium source. Cement can also be used. There is no particular restriction on the means used in the mixing step as long as it is a means capable of mixing any one of the hardening assistants of the above-mentioned embodiments 1 to 7 with the calcium source. The hardener obtained by mixing hardens in the presence of water.
[0063] [Method of manufacturing the hardened body] The method for producing a hardened body of the present embodiment includes a step of mixing raw materials containing at least the hardening aid of any one of the first to seventh embodiments, a calcium source, and water, a molding step, and a curing step. A hydraulic hardened body is obtained by the reaction of the hardening aid, which is a pozzolan, with the calcium source in the presence of water. The hardening aid and calcium source are as described above in the hardening agent. As described above, the calcium source may be any compound that releases calcium ions under wet conditions. The above-mentioned surface-modified lime may be used as the calcium source. Cement may also be used.
[0064] The raw materials are not limited to the hardening agent, calcium source, and water, but may also include aggregates. They may also include admixtures and additives. The aggregate may be a general aggregate used in concrete. By using aggregate separated from shirasu by the technique of Patent No. 6458267, shirasu can be effectively utilized. In addition, by using volcanic glass fine particles having a volcanic glass content of 80% or more obtained by dry specific gravity separation from shirasu, a volcanic eruption product, by the technique of Patent No. 6458267, or volcanic glass fine particles obtained by classifying volcanic ash or volcanic rock produced by quenching magma, as the aggregate, shirasu can be effectively utilized. In addition, by using shirasu balloons or a fired foam called perlite, which are fired and foamed from volcanic glass fine particles having a volcanic glass content of 80% or more obtained by dry specific gravity separation from shirasu, a volcanic eruption product, by the technique of Patent No. 6458267, or volcanic glass fine particles obtained by classifying volcanic ash or volcanic rock produced by quenching magma, as the aggregate, shirasu can be effectively utilized. Furthermore, it is also possible to use regolith, which has a composition similar to that of volcanic ejecta, as the aggregate, or the above-mentioned surface-modified lime as the aggregate.
[0065] The aggregate may be slaked lime. It is also possible to produce a hardened product that does not contain ordinary aggregates and is essentially made of only volcanic glass and slaked lime derived from volcanic eruptions. Furthermore, as mentioned above, by using sand or glass granules obtained by classifying shirasu using the technology of Patent No. 6458267 mentioned above, or shirasu balloons or perlite obtained by heating and foaming the glass granules, etc. as aggregate, it is possible to obtain a hardened body using shirasu as the raw material except for the calcium source, thereby enabling even more effective use of the shirasu.
[0066] When the calcium source is calcium hydroxide, the ratio of the total amount of (A) hardening agent (dry mass) and (B) calcium source (mass) to (C) aggregate (mass), expressed as a percentage, i.e., {(A)+(B)}×100 / (C), is preferably 25% or more. If it is less than 25%, it is difficult to obtain sufficient compressive strength when the mixture is hardened.
[0067] When mixing the hardening aid, aggregate, and calcium source, it is preferable to mix thoroughly so that they are uniformly dispersed. As described above, by using a dried hardening aid, handling during mixing can be made easier. Water is added to this mixture, and the mixture is mixed, molded, and cured to obtain a hardened body.
[0068] When forming, it can be filled into a formwork as necessary, formed, and demolded. In other words, the hardening aid, hardener, and hardened product of the present invention can be used to create buildings in the same way as ordinary concrete. The hardened product of the present invention is quick-setting, so it can be applied to secondary products using accelerated curing such as pressurized molded products and pressurized steam curing, as well as to automated construction structures using 3D printing technology that require a fast hardening speed.
[0069] When the mixture is filled into a formwork and molded, sufficient strength can be obtained by pouring it under normal pressure, just like in normal concrete manufacturing. Furthermore, the strength can be further increased by molding it under pressure.
[0070] Curing can be carried out in water, in a moist environment, or in the air at room temperature, as in the case of ordinary concrete production. During this curing, the active layer on the surface of the aluminosilicate activated particles in the hardening aid reacts with the calcium source to produce particles covered with calcium aluminosilicate, while the aluminosilicate sol in the hardening aid reacts with the calcium source to produce calcium silicate hydrate. The calcium aluminosilicate hydrate fills the gaps in the aggregate, strengthening the bonds and resulting in a hardened body with high strength. Curing in water can be done at a temperature of 20°C ± 5°C, which is standard for curing concrete. Curing can also be done in a pressurized steam atmosphere, which is used for concrete and building materials. During curing, in addition to the pozzolanic reaction that produces calcium silicate hydrate, a carbonation reaction occurs that absorbs and fixes carbon dioxide in the air, making the hardened body denser and improving its strength.
[0071] The hardened body after curing has a compressive strength equivalent to that of ordinary concrete of roughly 10 to 30 MPa, depending on the materials and curing conditions. It can reduce carbon dioxide emissions, including during the raw material manufacturing process, and is thought to be suitable for applications such as buildings and civil engineering works, where domestic resources can be effectively utilized. EXAMPLES
[0072] Next, the present invention will be described in more detail by comparing examples with comparative examples, but the present invention is not limited to these examples in any way.
[0073] Comparative Example 1 Volcanic glass fine particles with a particle size of 0.084 mm (volcanic glass content 88% by mass) were dry-gravity separated from volcanic eruptive shirasu. These were then crushed to obtain 50 parts by weight of volcanic glass fine powder with a particle size of 0.007 mm (volcanic glass content 87% by mass), and 50 parts by weight of calcium hydroxide. The mixture was poured into a mold, molded, and cured underwater. The apparent density of the paste hardened body at 14 days old was 1.18 g / cm. 3 The compressive strength measured using an AG-100KNA manufactured by Shimadzu Corporation was 2.5 MPa.
[0074] Comparative Example 2 A mixture of 100 parts by weight of volcanic glass granules with a particle size of 0.069 mm (volcanic glass content 85% by mass), 26 parts by weight of volcanic glass fine powder with a particle size of 0.007 mm (volcanic glass content 87% by mass), 30 parts by weight of calcium hydroxide, and 62 parts by weight of water was poured into a mold and cured underwater. The apparent density of the hardened body at 14 days old was 1.34 g / cm. 3 , and the compressive strength was 3.4 MPa.
[0075] Comparative Example 3 100 parts by weight of crushed limestone sand (produced in Oita Prefecture) with a particle size of 0.031 mm was mixed with 25 parts by weight of fine volcanic glass powder with a particle size of 0.007 mm (volcanic glass content 87% by mass), 33 parts by weight of ordinary Portland cement (manufactured by Sumitomo Osaka Cement), 5 parts by weight of fine volcanic glass powder with a particle size of 0.002 mm (volcanic glass content 84% by mass), and 44 parts by weight of water to obtain a hardened body by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.81 g / cm. 3 , and the compressive strength was 24.8 MPa.
[0076] Comparative Example 4 100 parts by weight of crushed limestone sand (produced in Oita Prefecture) with a particle size of 0.031 mm was mixed with 25 parts by weight of fine volcanic glass powder with a particle size of 0.007 mm (volcanic glass content 87% by mass), 33 parts by weight of hydraulic lime (NHL5 made in France), 5 parts by weight of fine volcanic glass powder with a particle size of 0.002 mm (volcanic glass content 84% by mass), and 45 parts by weight of water to obtain a hardened body by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.77 g / cm. 3 , the compressive strength was 4.7 MPa.
[0077] Comparative Example 5 A mixture of 100 parts by weight of volcanic glass granules with a particle size of 0.069 mm (volcanic glass content 85% by mass), 26 parts by weight of fine volcanic glass powder with a particle size of 0.007 mm (volcanic glass content 87% by mass), 33 parts by weight of calcium hydroxide, 6 parts by weight of fine volcanic glass powder with a particle size of 0.002 mm (volcanic glass content 84% by mass), and 66 parts by weight of water was poured into a mold and wet cured. The apparent density of the hardened body at 14 days old was 1.38 g / cm. 3 , and the compressive strength was 3.0 MPa.
[0078] Comparative Example 6 A mixture of 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm, 26 parts by weight of fly ash (manufactured by Kyushu Electric Power Co.'s Reihoku Power Station, Type II) with a particle size of 0.012 mm, 34 parts by weight of calcium hydroxide, and 37 parts by weight of water was poured into a formwork and cured underwater. The apparent density of the hardened material at 7 days of age was 1.61 g / cm. 3, and the compressive strength was 0.9 MPa.
[0079] Comparative Example 7 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm was mixed with 33 parts by weight of ordinary Portland cement (manufactured by Sumitomo Osaka Cement) and 23 parts by weight of water, and a hardened body was obtained by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.92 g / cm. 3 The compressive strength was 21.4 MPa. A hardened body was obtained by mixing 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm with 3 parts by weight of Meiko 610 (made by Pozzolith), 30 parts by weight of ordinary Portland cement (made by Sumitomo Osaka Cement), and 23 parts by weight of water, in the same manner. The apparent density of the hardened body was 1.90 g / cm. 3 , and the compressive strength was 26.7 MPa.
[0080] Example 1 8 g of volcanic glass fine powder with a particle size of 0.007 mm (volcanic glass content 87% by mass) was added to 48 mL of 1 mol / L aqueous sodium hydroxide solution and heated and stirred at 98°C under atmospheric pressure for 16 hours to obtain a suspension. 8.6 mL of 3.6 mol / L sulfuric acid was added to the suspension while heating it to 50°C to obtain an activated suspension with a pH of 4. The activated suspension was air-dried for one day to obtain a dehydrated activated suspension. A paste hardened body was obtained by mixing 66 parts by weight of water with a total of 100 parts by weight of 50 parts by weight of the dehydrated activated suspension and 50 parts by weight of calcium hydroxide, using the same process as in Comparative Example 1. The apparent density of the paste hardened body was 1.13 g / cm 3 The compressive strength was 4.1 MPa.
[0081] Example 2 The activated suspension obtained in the same manner as in Example 1 was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate activated particles. The aluminosilicate activated particles were air-dried for one day to obtain dehydrated aluminosilicate activated particles. 50 parts by weight of the dehydrated aluminosilicate activated particles and 50 parts by weight of calcium hydroxide (100 parts by weight in total) were mixed with 72 parts by weight of water to obtain a paste hardened body in the same manner as in Comparative Example 1. The apparent density of the paste hardened body was 1.18 g / cm. 3 , and the compressive strength was 9.4 MPa.
[0082] Example 3 A suspension obtained in the same manner as in Example 1 was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate particles. 13 g of the aluminosilicate particles were heated to 50°C while 1.2 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7. The high-density aluminosilicate activated particles were air-dried for one day to obtain dehydrated high-density aluminosilicate activated particles. A paste hardened body was obtained in the same manner as in Comparative Example 1 by mixing 59 parts by weight of water with 48 parts by weight of the dehydrated high-density aluminosilicate activated particles and 52 parts by weight of calcium hydroxide (100 parts by weight in total). The apparent density of the paste hardened body was 1.32 g / cm 3 , and the compressive strength was 10.2 MPa.
[0083] Example 4 The activated suspension obtained in the same manner as in Example 1 was centrifuged at 3000 rpm for 30 minutes to obtain an aluminosilicate sol. The aluminosilicate sol was air-dried for one day to obtain an aluminosilicate gel. 50 parts by weight of the aluminosilicate gel and 50 parts by weight of calcium hydroxide (total of 100 parts by weight) were mixed with 84 parts by weight of water to obtain a paste hardened body in the same manner as in Comparative Example 1. X-ray diffraction measurement of the paste hardened body confirmed the presence of calcium silicate hydrate.
[0084] Example 5 High-density aluminosilicate activated particles with a solid content concentration of 45% by mass were obtained in the same process as in Example 3. 47 parts by weight of the high-density aluminosilicate activated particles and 53 parts by weight of calcium hydroxide (100 parts by weight in total) were mixed with 21 parts by weight of water in terms of dry weight conversion, and a paste hardened body was obtained in the same process as in Comparative Example 1. The apparent density of the paste hardened body was 1.26 g / cm 3 , and the compressive strength was 8.6 MPa.
[0085] Example 6 High-density aluminosilicate activated particles with a solid content concentration of 45% by mass were obtained in the same process as in Example 3. 57 parts by weight of the high-density aluminosilicate activated particles and 43 parts by weight of calcium hydroxide (converted into dry weight) were mixed with 5 parts by weight of water for a total of 100 parts by weight, and a paste hardened body was obtained in the same process as in Comparative Example 1. The apparent density of the paste hardened body was 1.33 g / cm 3 , and the compressive strength was 11.0 MPa.
[0086] Example 7 8 g of volcanic glass fine powder (volcanic glass content 87% by mass) with a particle size of 0.007 mm was added to 48 mL of 1 mol / L sodium hydroxide solution and heated and stirred at 98°C under atmospheric pressure for 4 hours and 30 minutes to obtain a suspension. 8.6 mL of 3.6 mol / L sulfuric acid was added to the suspension while heating it to 85°C to obtain an activated suspension with a pH of 4. The activated suspension was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate activated particles with a solid content concentration of 33% by mass. 100 parts by weight of volcanic glass fine particles (volcanic glass content 88% by mass) with a particle size of 0.084 mm were mixed with 20 parts by weight of aluminosilicate activated particles in terms of dry weight, 34 parts by weight of calcium hydroxide, and 47 parts by weight of water to obtain a hardened body by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.20 g / cm 3 The compressive strength was 7.0 MPa.
[0087] Example 8 A suspension obtained in the same manner as in Example 7 was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate particles. 11 g of the aluminosilicate particles were heated to 55°C and 1 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content of 43 mass%. 100 parts by weight of volcanic glass fine particles with a particle size of 0.084 mm (volcanic glass content of 88 mass%) were mixed with 29 parts by weight of high-density aluminosilicate activated particles, calculated as a dry weight, 33 parts by weight of calcium hydroxide, and 29 parts by weight of water to obtain a hardened body in the same manner as in Comparative Example 2. The apparent density of the hardened body was 1.53 g / cm. 3 , and the compressive strength was 14.5 MPa.
[0088] Example 9 12 g of aluminosilicate particles obtained in the same manner as in Example 3 were heated to 50°C while 1.1 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7. The high-density aluminosilicate activated particles were air-dried for one day to obtain dehydrated high-density aluminosilicate activated particles. 23 parts by weight of dehydrated high-density aluminosilicate activated particles, 29 parts by weight of calcium hydroxide, and 64 parts by weight of water were mixed with 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content 85% by mass), and a hardened body was obtained in the same manner as in Comparative Example 2. The apparent density of the hardened body was 1.43 g / cm. 3 , and the compressive strength was 11.5 MPa.
[0089] Example 10 High-density aluminosilicate activated particles with a pH of 7 and a solid content of 44% by mass were obtained by the same process as in Example 3. 100 parts by weight of crushed lime sand (produced in Oita Prefecture) with a particle size of 0.031 mm were mixed with 22 parts by weight of high-density aluminosilicate activated particles (converted into dry weight), 33 parts by weight of ordinary Portland cement (manufactured by Sumitomo Osaka Cement), 5 parts by weight of volcanic glass fine powder with a particle size of 0.002 mm (volcanic glass content of 84% by mass), and 24 parts by weight of water, and a hardened body was obtained by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.83 g / cm. 3 , and the compressive strength was 29.8 MPa.
[0090] Example 11 High-density aluminosilicate activated particles with a pH of 7 and a solid content of 45% by mass were obtained by the same process as in Example 3. 100 parts by weight of mortar-ground limestone sand (produced in Oita Prefecture) with a particle size of 0.031 mm were mixed with 22 parts by weight of high-density aluminosilicate activated particles (converted into dry weight), 33 parts by weight of hydraulic lime (NHL5 made in France), 5 parts by weight of volcanic glass fine powder with a particle size of 0.002 mm (volcanic glass content of 84% by mass), and 24 parts by weight of water, and a hardened body was obtained by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.72 g / cm. 3 , and the compressive strength was 12.5 MPa.
[0091] Example 12 8 g of volcanic glass fine powder (volcanic glass content 87% by mass) with a particle size of 0.007 mm was added to 48 mL of 0.5 mol / L sodium hydroxide solution and heated and stirred at 98°C under atmospheric pressure for 19 hours and 30 minutes to obtain a suspension. The suspension was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate particles. 0.5 mL of 3.6 mol / L sulfuric acid was added to 12 g of the aluminosilicate particles while heating them to 50°C to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 47% by mass. 100 parts by weight of volcanic glass fine particles (volcanic glass content 85% by mass) with a particle size of 0.069 mm were mixed with 24 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 33 parts by weight of calcium hydroxide, and 48 parts by weight of water to obtain a hardened body by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.41 g / cm 3 , and the compressive strength was 9.9 MPa.
[0092] (Example 13) 8 g of volcanic glass fine powder (volcanic glass content 87%) with a particle size of 0.007 mm was added to 48 mL of 3 mol / L sodium hydroxide solution and heated and stirred at 98 ° C under atmospheric pressure for 4 hours and 30 minutes to obtain a suspension. The suspension was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate particles. 12 g of the aluminosilicate particles were heated to 50 ° C and 1.7 mL of 7.2 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 6 and a solid content concentration of 42 mass %. A hardened body was obtained by the same process as in Comparative Example 2 for a mixture of 21 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 33 parts by weight of calcium hydroxide, 6 parts by weight of volcanic glass fine powder with a particle size of 0.002 mm (volcanic glass content 84 mass %), and 46 parts by weight of water, relative to 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content 85 mass %). The apparent density of the hardened body is 1.38 g / cm 3 , and the compressive strength was 10.0 MPa.
[0093] Example 14 12 g of aluminosilicate particles obtained in the same manner as in Example 3 were heated to 50°C and 1.0 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 3 and a solid content concentration of 45% by mass. 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content of 85% by mass) were mixed with 23 parts by weight of high-density aluminosilicate activated particles (calculated as dry weight), 33 parts by weight of calcium hydroxide, 6 parts by weight of volcanic glass fine powder with a particle size of 0.002 mm (volcanic glass content of 84% by mass) and 38 parts by weight of water to obtain a hardened body in the same manner as in Comparative Example 5. The apparent density of the hardened body was 1.54 g / cm. 3 , and the compressive strength was 12.2 MPa.
[0094] Example 15 6 g of aluminosilicate particles obtained in the same manner as in Example 8 were heated to 50°C and 0.3 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 11 and a solid content concentration of 48 mass%. 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content of 85 mass%) were mixed with 24 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 33 parts by weight of calcium hydroxide, and 48 parts by weight of water, and a hardened body was obtained in the same manner as in Comparative Example 2. The apparent density of the hardened body was 1.43 g / cm 3 , and the compressive strength was 10.6 MPa.
[0095] (Example 16) A mixture of 31 parts by weight (in dry weight equivalent) of high-density aluminosilicate activated particles obtained in the same manner as in Example 3, 69 parts by weight of calcium hydroxide, totaling 100 parts by weight, and 32 parts by weight of water was used to obtain a paste hardened body in the same manner as in Comparative Example 1. The apparent density of the paste hardened body was 1.26 g / cm. 3 , and the compressive strength was 8.0 MPa.
[0096] (Example 17) 13 g of aluminosilicate particles obtained in the same process as in Example 3 were heated to 50°C and 1.2 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 45 mass%. 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content of 85 mass%) were mixed with 9 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 20 parts by weight of calcium hydroxide, and 41 parts by weight of water, and a hardened body was obtained in the same process as in Comparative Example 2. The apparent density of the hardened body was 1.34 g / cm 3 , and the compressive strength was 4.9 MPa.
[0097] (Example 18) 8 g of volcanic glass fine powder (volcanic glass content 85% by mass) with a particle size of 0.050 mm was added to 48 mL of 1 mol / L sodium hydroxide solution and heated and stirred at 98 ° C under atmospheric pressure for 4 hours and 30 minutes to obtain a suspension. The suspension was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate particles. 12 g of the aluminosilicate particles were heated to 50 ° C and 1.1 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 43% by mass. 21 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 33 parts by weight of calcium hydroxide, 6 parts by weight of volcanic glass fine powder with a particle size of 0.002 mm (volcanic glass content 84% by mass), and 37 parts by weight of water were mixed with 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content 85% by mass), and a hardened body was obtained by the same process as in Comparative Example 5. The apparent density of the hardened body is 1.50 g / cm 3 , and the compressive strength was 11.3 MPa.
[0098] (Example 19) 12 g of aluminosilicate particles obtained in the same process as in Example 8 were heated to 50°C and 1.1 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 45% by mass. 100 parts by weight of volcanic glass fine particles with a particle size of 0.069 mm (volcanic glass content of 85% by mass) were mixed with 22 parts by weight of high-density aluminosilicate activated particles (on a dry weight basis), 33 parts by weight of calcium hydroxide, 6 parts by weight of volcanic glass fine powder with a particle size of 0.002 mm (volcanic glass content of 84% by mass), and 36 parts by weight of water, and the mixture was poured into a mold and wet cured. The apparent density of the hardened body at 14 days of age was 1.56 g / cm. 3 The compressive strength was 10.5MPa. The apparent density of the hardened material produced in the same process after 33 days was 1.57g / cm 3 , and the compressive strength was 14.6 MPa.
[0099] (Example 20) 8 g of volcanic glass fine powder (volcanic glass content 87% by mass) with a particle size of 0.007 mm was added to 48 mL of 1 mol / L sodium hydroxide solution and heated and stirred at 98 ° C under atmospheric pressure for 14 hours to obtain a suspension. The suspension was centrifuged at 3000 rpm for 30 minutes to obtain aluminosilicate particles. 11 g of the aluminosilicate particles were heated to 50 ° C while adding 1 mL of 3.6 mol / L sulfuric acid to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 45% by mass. 100 parts by weight of volcanic glass fine particles (volcanic glass content 85% by mass) with a particle size of 0.069 mm were mixed with 23 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 33 parts by weight of calcium hydroxide, and 46 parts by weight of water to obtain a hardened body by the same process as in Comparative Example 2. The apparent density of the hardened body was 1.45 g / cm 3 The compressive strength was 10.7 MPa. In addition, by adding 6 parts of volcanic glass fine powder (volcanic glass content 84% by mass) with a particle size of 0.002 mm in the same manner and adding 51 parts by weight of water, the apparent density of the hardened body was 1.50 g / cm. 3 , and the compressive strength was 14.7 MPa.
[0100] Example 21 High-density aluminosilicate activated particles with a solid content concentration of 45% by mass were obtained in the same manner as in Example 3. 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm were mixed with 22 parts by weight of high-density aluminosilicate activated particles, calculated as a dry weight, 33 parts by weight of calcium hydroxide, 5 parts by weight of aluminum hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 26 parts by weight of water, and a hardened body was obtained in the same manner as in Comparative Example 2. The apparent density of the hardened body was 1.72 g / cm. 3 , and the compressive strength was 14.4 MPa.
[0101] Example 22 A suspension obtained in the same manner as in Example 1 was centrifuged at 1000 rpm for 30 minutes to obtain aluminosilicate particles. 13 g of the aluminosilicate particles were heated to 50°C while 1.2 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7. 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm were mixed with 22 parts by weight of the high-density aluminosilicate activated particles, calculated as a dry weight, 26 parts by weight of calcium hydroxide, and 16 parts by weight of water, and a hardened body was obtained in the same manner as in Comparative Example 2. The apparent density of the hardened body was 1.82 g / cm. 3 , and the compressive strength was 18.1 MPa.
[0102] (Example 23) The suspension obtained in the same manner as in Example 1 was centrifuged at 2000 rpm for 30 minutes to obtain aluminosilicate particles. 12 g of the aluminosilicate particles were heated to 50°C and 1.2 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7. 100 parts by weight of Toyoura silica sand (Yamaguchi Prefecture) with a particle size of 0.26 mm was mixed with 22 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, and calcium carbonate fertilizer (Tokunoshima Coral, Tokunoshima, Kagoshima Prefecture) was heat-treated in a medium fluidized bed at 1,000°C for 1 second or less using a shirasu balloon manufacturing device (Nishinaka Seisakusho Co., Ltd.), and the surface of the particles was quickly calcified and collected in a cyclone dust collector. The mixture was mixed with 34 parts by weight of surface-modified lime powder with an average particle size of 25.9 μm and 16 parts by weight of water to obtain a hardened body in the same manner as in Comparative Example 2. The apparent density of the hardened body was 1.75 g / cm. 3 , and the compressive strength was 19.1 MPa.
[0103] Example 24 8 g of fly ash (Kyushu Electric Power Reihoku Power Plant, Type II) with a particle size of 0.012 mm was added to 48 mL of 1 mol / L sodium hydroxide solution and heated and stirred at 98°C under atmospheric pressure for 16 hours to obtain a suspension. The suspension was centrifuged at 2000 rpm for 30 minutes to obtain aluminosilicate particles. 18 g of the aluminosilicate particles were heated to 50°C and 1.9 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 45 mass%. 100 parts by weight of Toyoura silica sand (Yamaguchi Prefecture) with a particle size of 0.26 mm were mixed with 23 parts by weight of high-density aluminosilicate activated particles in terms of dry weight, 34 parts by weight of calcium hydroxide, and 16 parts by weight of water, and the mixture was poured into a mold and molded, followed by underwater curing. The apparent density of the hardened body at 7 days was 1.75 g / cm 3 , and the compressive strength was 18.4 MPa.
[0104] (Example 25) The high-density aluminosilicate activated particles obtained in the same process as in Example 23 were dried for one day to obtain dehydrated high-density aluminosilicate activated particles. 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm were mixed with 3 parts by weight (dry weight equivalent) of the high-density aluminosilicate activated particles, 30 parts by weight of ordinary Portland cement (manufactured by Sumitomo Osaka Cement), and 23 parts by weight of water to obtain a hardened body in the same process as in Comparative Example 2. The apparent density of the hardened body was 1.97 g / cm. 3 , and the compressive strength was 28.7 MPa.
[0105] (Example 26) 8 g of volcanic glass fine powder (volcanic glass content 87% by mass) with a particle size of 0.007 mm was added to 48 mL of 1 mol / L sodium hydroxide solution and heated and stirred at 98 ° C for 4 hours and 30 minutes under atmospheric pressure to obtain a suspension. The suspension was centrifuged at 2000 rpm for 30 minutes to obtain aluminosilicate particles. 14 g of the aluminosilicate particles were heated to 50 ° C and 1.4 mL of 3.6 mol / L sulfuric acid was added to obtain high-density aluminosilicate activated particles with a pH of 7 and a solid content concentration of 45% by mass. The electrical conductivity of the suspension prepared with distilled water to a solid content concentration of 11% by mass was 1460 mS / m. The obtained high-density aluminosilicate activated particles were added with 4 times the amount of distilled water and stirred, and then centrifuged at 3000 rpm for 30 minutes to settle, and this operation was repeated three times to obtain dealkalized high-density aluminosilicate activated particles. The electrical conductivity of the suspension prepared with distilled water to a solid content concentration of 11% by mass was 28.3 mS / m. The obtained dealkalized high density aluminosilicate activated particles were air-dried for 2 days to obtain dehydrated dealkalized high density aluminosilicate activated particles. 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm was mixed with 3 parts by weight of the dehydrated dealkalized high density aluminosilicate activated particles, 30 parts by weight of ordinary Portland cement (manufactured by Sumitomo Osaka Cement Co., Ltd.) and 25 parts by weight of water, and the mixture was poured into a formwork for molding and cured underwater. The apparent density of the hardened body at 91 days of age was 1.95 g / cm. 3 , and the compressive strength was 39.5 MPa.
[0106] Example 27 8 g of fine volcanic glass powder with a particle size of 0.007 mm (volcanic glass content: 87% by mass) was added to 48 mL of 1 mol / L aqueous sodium hydroxide solution and heated and stirred at 98°C under atmospheric pressure for 4 hours and 30 minutes to obtain a suspension. The suspension was heated to 85°C and 8.6mL of 3.6mol / L sulfuric acid was added to obtain an activated suspension with a pH of 4. The activated suspension was centrifuged at 3000rpm for 30 minutes to obtain aluminosilicate activated particles with a solid content of 33% by mass. The electrical conductivity of the suspension prepared with distilled water to obtain a solid content of 11% by mass was 1639mS / m. The obtained aluminosilicate activated particles were added with four times the amount of distilled water, stirred, and then centrifuged at 3000rpm for 30 minutes to allow sedimentation, and this operation was repeated three times to obtain dealkalized aluminosilicate activated particles. The electrical conductivity of the suspension prepared with distilled water to obtain a solid content of 11% by mass was 34.7mS / m. The obtained dealkalized aluminosilicate activated particles were air-dried for two days to obtain dehydrated dealkalized aluminosilicate activated particles. A mixture of 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm, 3 parts by weight of dehydrated and dealkalized aluminosilicate activated particles, 30 parts by weight of ordinary Portland cement (produced by Sumitomo Osaka Cement Co., Ltd.), and 25 parts by weight of water was poured into a formwork and cured underwater. The apparent density of the hardened body at 28 days of age was 1.93 g / cm. 3 , and the compressive strength was 31.6 MPa.
[0107] (Example 28) 8 g of volcanic glass fine powder (volcanic glass content 87% by mass) with a particle size of 0.007 mm was added to 48 mL of 1 mol / L sodium hydroxide solution and heated and stirred at 98 ° C for 4 hours and 30 minutes under atmospheric pressure to obtain a suspension. The suspension was centrifuged at 2000 rpm for 30 minutes to obtain aluminosilicate particles. 50 g of distilled water was added to 14 g of the aluminosilicate particles, and carbon dioxide gas with a purity of 99.9 volume% was blown in at a flow rate of 10 mL / min for 20 hours while stirring to obtain aluminosilicate activated particles. The electrical conductivity of the suspension prepared with distilled water to a solid content concentration of 11% by mass was 1085 mS / m. Four times the amount of distilled water was added to the obtained aluminosilicate activated particles, and the mixture was stirred, followed by centrifuging at 3000 rpm for 30 minutes to allow sedimentation. This operation was repeated three times to obtain dealkalized aluminosilicate activated particles. The electrical conductivity of a suspension prepared with distilled water to a solids concentration of 11% by mass was 56.9 mS / m. The obtained dealkalized aluminosilicate activated particles were air-dried for two days to obtain dehydrated dealkalized aluminosilicate activated particles. 100 parts by weight of Toyoura silica sand (produced in Yamaguchi Prefecture) with a particle size of 0.26 mm was mixed with 3 parts by weight of the dehydrated dealkalized aluminosilicate activated particles, 30 parts by weight of ordinary Portland cement (manufactured by Sumitomo Osaka Cement Co., Ltd.) and 25 parts by weight of water, and the mixture was poured into a formwork and cured in water. The apparent density of the hardened body at 28 days was 1.95 g / cm. 3 , and the compressive strength was 29.6 MPa.
Claims
1. A hardening aid comprising aluminosilicate activated particles and aluminosilicate sol, the hardening aid being produced by adding an inorganic acid to a suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic eruptions or artificial pozzolan.
2. A hardening aid comprising aluminosilicate activated particles (including dealkalized aluminosilicate activated particles) of the solid phase obtained by solid-liquid separation from an activated suspension produced by adding an inorganic acid to a suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan.
3. A hardening aid comprising aluminosilicate activated particles (including dealkalized aluminosilicate activated particles) which have been activated by adding an inorganic acid to aluminosilicate particles in the solid phase which have been separated from a suspension produced by the heating and alkali treatment of volcanic glass material derived from volcanic ejecta or artificial pozzolan.
4. A hardening aid containing aluminosilicate sol from the liquid phase obtained by solid-liquid separation of an activated suspension produced by adding inorganic acid to a suspension produced by the heated alkali treatment of volcanic glass derived from volcanic eruptions or artificial pozzolan.
5. A hardening aid containing an aluminosilicate sol that is activated by adding an inorganic acid to the liquid phase of the solid-liquid separated suspension produced by the heating and alkali treatment of volcanic glass derived from volcanic ejecta or artificial pozzolan.
6. The curing aid according to any one of claims 1 to 5, which has been dried.
7. The hardening aid according to any one of claims 1 to 3, wherein the aluminosilicate activated particles are particles having a core of either or both of volcanic glass and zeolite, the surface of which is covered with aluminosilicate gel, and the aluminosilicate gel is dissolved and precipitated from the core to form an active layer on the surface of the particles.
8. A method for producing a hardening aid, comprising the steps of heating and mixing volcanic glass or artificial pozzolan derived from volcanic ejecta with an alkaline solution to produce a suspension, and adding an inorganic acid to one or both of the solid and liquid phases of the suspension.
9. The method for producing a curing auxiliary according to claim 8, further comprising a step of subjecting the solid phase of the suspension to a dealkalization treatment.
10. 9. The method for producing a curing aid according to claim 8, further comprising the step of subjecting the obtained activated suspension to solid-liquid separation after the step of adding an inorganic acid to both the solid phase and the liquid phase of the suspension, to obtain the aluminosilicate activated particles of the solid phase.
11. The method for producing a curing assistant according to claim 9, further comprising a step of subjecting the solid phase aluminosilicate activated particles to a dealkalization treatment.
12. 9. The method for producing a curing aid according to claim 8, further comprising the step of subjecting the obtained activated suspension to solid-liquid separation after the step of adding an inorganic acid to both the solid phase and the liquid phase of the suspension, to obtain an aluminosilicate sol of the liquid phase.
13. The method for producing the curing aid according to any one of claims 8 to 12, further comprising a step of drying.
14. A hardening agent comprising the hardening aid according to any one of claims 1 to 5 and a calcium source.
15. 15. The hardener of claim 14, wherein the calcium source is surface-modified lime or cement.
16. A hardening agent comprising the hardening aid according to claim 6 and a calcium source.
17. 17. The hardener of claim 16, wherein the calcium source is surface-modified lime or cement.
18. A method for producing a hardener, comprising the step of mixing the hardening aid according to any one of claims 1 to 5 with a calcium source.
19. The method for producing a hardener according to claim 18, wherein the calcium source is surface-modified lime or cement.
20. A method for producing a hardener, comprising the step of mixing the hardening aid according to claim 6 with a calcium source.
21. 21. The method for producing a hardener according to claim 20, wherein the calcium source is surface-modified lime or cement.
22. A method for producing a hardened body, comprising the steps of: mixing raw materials comprising the hardening aid according to any one of claims 1 to 5, a calcium source, and water; forming the raw materials; and curing the raw materials.
23. 7. A method for producing a hardened body, comprising the steps of mixing raw materials comprising the hardening aid according to claim 6, a calcium source, and water, forming the raw materials, and curing the raw materials.
24. The method for producing a hardened body according to claim 22, wherein the calcium source is a compound that releases calcium ions when wet.
25. The method for producing a hardened body according to claim 23, wherein the calcium source is a compound that releases calcium ions when wet.
Citation Information
Patent Citations
Hydraulic lime composition
JP2013519616A